Pengembangan Edible Sensor Berbasis Antosianin Kubis Merah (Brassica oleracea var capitata L.) untuk Monitoring Kesegaran Fillet Ikan Nila (Oreochromis niloticus) - Hadiyatun Nuroniyah; Bambang Kuswandi; Ayik Rosita Puspaningtyas (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Tilapia is actually the most popular source of protein in the world market in the form of fillets, because it has several advantages, such as being able to be processed into various new processed products, easy to distribute and marketable in attractive forms. It is necessary to monitor the freshness quality of tilapia fish fillets. This study aims to develop an edible sensor for monitoring the freshness of tilapia (Oreochromis niloticus) fillets that are safe for consumption and also environmentally friendly with a pH indicator of the anthocyanin of red cabbage (Brassica Oleracea Var. Capitata L.). The edible sensor was applied to the tilapia fillet package. The characterization of edible sensors includes observation of surface morphology with SEM and functional group analysis with FTIR. Tests for freshness parameters of tilapia fish fillets included pH value test, total microbial count test, TVBN level test, and organoleptic test. The color change of the edible sensor was observed visually and using ImageJ software to determine the mean red value. The results show that the color of the edible sensor is dark purple when it indicates fresh tilapia fillet, the light purple color is still fresh, and the grayish-purple color of rotten tilapia fillet is not safe for consumption. Red cabbage anthocyanin-based edible sensors can be applied as smart labels for monitoring the freshness of tilapia fillets.